PEDAGOGICAL PRINCIPLES OF THE DESIGN AND DEVELOPMENT OF EXPERT TRAINING SYSTEMS - Oleh Shevchuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The articles defines the system of pedagogical principles (centering on an individual, the priority of the pedagogical approach, educational appropriateness of the use of new information technologies; the freedom of choice of the cognitive trajectory; diversity; openness and development; professional orientation; "precedent", the emotional fulfillment of the environment; the distribution of educational material) which has to lie on the basis of designingeducational techniques which are based on expert training systems. The gnosiological grounds for the mentioned system of principles are provided.